A Note on Interaction between Groups and Convergence Spaces: Pranav Sharma - Team, Support (Thai Journal of Mathematics, 2022)
This note is devoted to present the idea to explore groups from the viewpoint of convergence spaces by identifying their Cayley graphs with a finitely generated pretopological space. The notion of continuity for groups is explored with some examples.